2002
DOI: 10.1002/gps.517
|View full text |Cite
|
Sign up to set email alerts
|

The DSM‐IV ‘minor depression’ disorder in the oldest‐old: prevalence rate, sleep patterns, memory function and quality of life in elderly people of Italian descent in Southern Brazil

Abstract: In this study, minor depression has been significantly associated with lower life satisfaction and worse indexes of life quality. The results supported the current concept that minor depression is prevalent in later life, especially among the oldest-old. Subjects with minor depression had worse self-reported opinions about memory and sleep patterns, but when these variables were objectively measured, no meaningful differences could be determined by the research team. Female gender and the concurring presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 34 publications
0
30
0
8
Order By: Relevance
“…De igual manera, diversos estudios han demostrado que los adultos mayores que tienen una peor calidad de vida se asocian con mayores prevalencias de depresión, ansiedad y déficit funcional (7,31,32). En este estudio, esto fue un hallazgo constante, pues las personas que tuvieron altos puntajes en las escalas de síntomas depresivos, de riesgo de ansiedad y déficit en la capacidad funcional, presentaron bajos puntajes de calidad de vida.…”
Section: Discussionunclassified
“…De igual manera, diversos estudios han demostrado que los adultos mayores que tienen una peor calidad de vida se asocian con mayores prevalencias de depresión, ansiedad y déficit funcional (7,31,32). En este estudio, esto fue un hallazgo constante, pues las personas que tuvieron altos puntajes en las escalas de síntomas depresivos, de riesgo de ansiedad y déficit en la capacidad funcional, presentaron bajos puntajes de calidad de vida.…”
Section: Discussionunclassified
“…Recent studies have shown that WHOQOL-Bref domain scores among the middle-aged and elderly are influenced by socio-demographic variables such as age and ethnicity 6 , depression 6,7,8,9 , suicidality 10 , psychotic symptoms 10 , depression associated with patients with chronic pain symptoms 9 , number of selfreported illnesses 8 , and self-health assessment 8 . These data suggest that the score obtained in the scale can be affected if taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, os indivíduos que avaliam a sua qualidade de vida como negativa apresentam significativamente mais sintomas depressivos do que aqueles que têm esperança; conforme alguns estudos, esses últimos apresentam melhores condições de saúde (Carpenito, 1995;Farran, Herth & Popovich, 1995;Miller, 1985). Outros estudos também têm encontrado uma associação entre má qualidade de vida e depressão (Herman et al, 2002;Kuehner, 2002;Xavier et al, 2002).…”
unclassified